Sosialisasi Kesadaran Keamanan Digital di Era Revolusi Industri 4.0 - Novia Ayu Sekar Pertiwi; Fitri Umardiyah; Muhammad Naufal Mansyur; Misbahul Munir; Imam Sapi’i; Amanathus Sholichah; Tisa Nailatu Fudlah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Dukuhdimoro Village, Mojoagung, Jombang, is the location of community service activities focusing on the socialization of digital security in the era of the Fourth Industrial Revolution. Through the Service Learning approach, this program aims to raise awareness among the community about cybercrime threats and how to protect themselves in the use of information technology. Involving various stakeholders such as students, youth from religious organizations, and village residents, the program provides information about digital crime risks and preventive measures that can be taken. Program evaluation indicates a significant increase in participants' understanding of digital crime and high learning interest among the community. Through the publication of the "Cyber Crime" book, the program also aims to empower the community with the knowledge and skills needed to address challenges in the digital age. Its impact extends to various aspects, including economic, social, and other sectors, by increasing awareness, data protection, and utilizing digital technology for community advancement. Awareness and proactive action to ensure digital security are key to supporting sustainable development in the era of the Fourth Industrial Revolution